The Influence of Service Quality and Infrastructure on the Level of Satisfaction of BPJS Physiotherapy Patients at Dompet Dhuafa Bogor Integrated Health Home Hospital: Pengaruh Kualitas Pelayanan dan Sarana Prasarana terhadap Tingkat Kepuasan Pasien BPJS Fisioterapi di RSUD Dompet Dhuafa Bogor - El Munadiyan, Aza; Nastasia, Etty Siswanty; Hendriana, Asep (YCMM, 2024)
This study aims to determine the influence of service quality and infrastructure on the level of satisfaction of BPJS physiotherapy patients at Dompet Dhuafa Integrated Health Home Hospital. The background to this research is based on preliminary findings regarding the assessment of satisfaction with outpatient services for physiotherapy patients during 2022, most of the monthly patient satisfaction scores are below hospital satisfaction standards. This research method is cross-sectional with a questionnaire survey method to collect primary data from 45 respondents received physiotherapy services with BPJS Health membership during the period June 2023 at RST Dompet Dhuafa Hospital. Analysis method used the correlation tests and coefficient of determination tests. The results of the research show that there is a very strong relationship between the quality of services and infrastructure and the level of satisfaction of BPJS physiotherapy patients at Dompet Dhuafa Integrated Health Home Hospital Bogor with a coefficient of determination of 84.7% and a correlation value of 0.921. This research expands knowledge regarding the quality of service and satisfaction of physiotherapy patients and provides important guidance for health service policy holders to improve the quality of physiotherapy services.